Hydration and beyond: neuropeptides as mediators of hydromineral balance, anxiety and stress-responsiveness - Smith, Justin A.; Pati, Dipanwita; Wang, Lei; de Kloet, Annette D.; Frazier, Charles J.; Krause, Eric G. (Frontiers in Systems Neuroscience, 2015)
Challenges to body fluid homeostasis can have a profound impact on hypothalamic regulation of stress responsiveness. Deficiencies in blood volume or sodium concentration leads to the generation of neural and humoral signals relayed through the hindbrain and circumventricular organs that apprise the paraventricular nucleus of the hypothalamus (PVH) of hydromineral imbalance. Collectively, these neural and humoral signals converge onto PVH neurons, including those that express corticotrophin-releasing factor, oxytocin, and vasopressin, to influence their activity and initiate compensatory responses that alleviate hydromineral imbalance. Interestingly, following exposure to perceived threats to homeostasis, select limbic brain regions mediate behavioral and physiological responses to psychogenic stressors, in part, by influencing activation of the same PVH neurons that are known to maintain body fluid homeostasis. Here, we review past and present research examining interactions between hypothalamic circuits regulating body fluid homeostasis and those mediating behavioral and physiological responses to psychogenic stress.